2020
DOI: 10.1016/j.resuscitation.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

First experience with the abdominal aortic and junctional tourniquet in prehospital traumatic cardiac arrest

Abstract: Introduction: The Abdominal Aortic and Junctional Tourniquet (AAJT) increased systemic vascular resistance, mean arterial pressure, carotid blood flow and rate of return of spontaneous circulation (ROSC) in animals with hypovolaemic traumatic cardiac arrest (TCA). The objective of this study was to report the first experience of the use of the AAJT as part of a pre-hospital TCA algorithm.Methods: This is a descriptive case series of the use of the AAJT in patients with TCA in a civilian physician-led pre-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The abdominal aortic and junctional tourniquet (AAJT) is a non-invasive alternative to endovascular balloon occlusion of the aorta. This device is applied to the lower abdomen, and the inflatable bladder functions to occlude the femoral arteries at the level of the umbilicus [ 15 ]. Animal studies using the AAJT as a CPR adjunct following traumatic and non-traumatic cardiac arrest found that it significantly increases truncal blood pressure [ 16 , 17 ] and improves survival outcomes [ 16 ] compared to animals receiving standard CPR.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal aortic and junctional tourniquet (AAJT) is a non-invasive alternative to endovascular balloon occlusion of the aorta. This device is applied to the lower abdomen, and the inflatable bladder functions to occlude the femoral arteries at the level of the umbilicus [ 15 ]. Animal studies using the AAJT as a CPR adjunct following traumatic and non-traumatic cardiac arrest found that it significantly increases truncal blood pressure [ 16 , 17 ] and improves survival outcomes [ 16 ] compared to animals receiving standard CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 studies included for JTQ review, eight were conducted in 194 healthy human volunteers [16][17][18][19][20][21][22][23] (Table 2), 3 were conducted on 16 perfused human cadavers [24][25][26] (Table 3), and 2 case series [27,28] and 1 case report [29] on 21 trauma patients (Table 4). The total number of cadavers and volunteers was 210.…”
Section: Pre-hospital Feasability Evidencementioning
confidence: 99%
“…The AAJT case series had a mortality rate of 100%, whereas the SJT and JETT case series had mortality rates of <25%. However, Balian et al [28] aimed to assess the effects of the AAJT on physiological parameters associated with traumatic cardiac arrest rather than reducing blood loss from a junctional or abdominal wound.…”
Section: Junctional Tourniquetsmentioning
confidence: 99%